Pengembangan Game Tajwid Berbasis Android - Khusnan Hidayat, Fauzan, Diah Priyawati, S.T., M.Eng (2017)
Many Muslim children are less able to read the Qur'an with true tajwid, A lot of application games are scattered in the google play store but do not have the awards and animation less so that less interested children.Development of Tajwid Game Based on Android is aimed to implement and design tajwid game based on Android,And to find out the response of children in the development of Android-based tajwid game, And developing games that are already there are still many do not give awards in it that make children less enjoy the game that already exists. This research uses research and development method. Game "tajwid based on Android developed with System Development Lifecircle (SDLC) mode.This research is covered in the Testimony at Kunti Andong Boyolali Mosque. The data collected were 14 data from the children who studied the law of reading tajwid ie age 8 years using a questionnaire whose analysis was done descriptively. This research is designed with the easy-to-use Construct 2 application in game development because it does not use special programming language. Construct 2 is an application used to create 2-Dimensional games based on HTML 5. The results of this research is a game that is easy to play and useful for the user. This game can also be installed on all android platforms.The evaluation of research success is measured through questionnaires and blackbox. Questionnaire results one of them achieving 88% presentation on the game questionnaire makes it easy to understand tajwid material.